On The Solutions of Some Difference Equations Systems and Analytical Properties - Tuz, Munevver (E D P Sciences, 2018)
In this study, we investigated the global asymptotic behaviors of their solutions by taking the second-order difference equation system. According to the given conditions, we obtained some asymptotic results for the positive balance of the system. We have also worked on q-fast changing functions. Such functions form the class of q-Caramate functions. We have applied q-Caramate functions to linear q-difference equations and We have also learned about the asymptotic behavior of solutions. In addition, we have studied the problem of initial and boundary value for the q-difference equation
3rd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 04-06, 2018 -- Final Int Univ, Girne, CYPRUS
Keywords: Quadratic Pencil